The biodegradable mGnRHa-Poly[lactic-co-glycolic acid] microparticles enhances semen quality in multi-stripped rainbow trout - Amin Mokhles Abadi Farahani; Fatemeh Paykan Heyrati; Mohammad Dinari; Hamid Reza Habibi; Salar Dorafshan (PLoS ONE, 2026)
To reduce reproduction costs, broodstock undergo multiple stripping, during which semen quality gradually declines toward the end of the spawning season. One potential solution is the use of slow-release delivery systems such as mGnRHa-PLGA (Poly[lactic-co-glycolic acid]) microparticles to prolong the spermiation period. In this study, mGnRHa microparticles with an average size of 14.77 ± 8.09 µm were prepared using an oil-in-water emulsion that release more than 72% of the mGnRHa within 61 days at 12°C. For the in vivo trial, during the end of the natural spawning season, 50 mature rainbow males (738.60 ± 104.86 g and 40.09 ± 2.03 cm) were randomly divided into 5 groups. The control group (C) received 1 mL kg -1 physiological saline. The second group (10A) received 10 μg kg -1 mGnRHa. The third to fifth groups (10M, 20M, and 40M) received 10, 20, and 40 μg kg -1 mGnRHa in the form of mGnRHa-PLGA microparticles, respectively. Semen and blood samples were collected at 0, 9, 21, 47, and 61 days days post injection (dpi) for semen quality and sex steroid hormones assessments. Only 40M group continued to release semen until 61 dpi. The 40M group showed the highest semen volume and sperm density throughout the experimental period, while no significant differences were observed between C, 10A, and 10M groups. At 21, 47, and 61 dpi, the 40M group exhibited the highest sperm density, semen volume, and plasma testosterone levels among all groups. At 61 dpi, 40M group showed the highest GSI and the largest surface area occupied by spermatids and spermatozoa. Finally, while the acute mGnRHa failed to enhance spermiation parameters under multiple stripping conditions, the 40M were capable of increasing the duration of semen release and boosting semen volume at the end of spawning season. This study provided aquaculturists with novel information to improve reproductive performance in rainbow trout hatcheries.